H. G. Huettich: Theater in the Planned Society: Contemporary Drama in its Historical, Political, and Cultural Context - Joan E Holmes (GDR Bulletin, 1978)
Chapel Hill, NC: Univ. of North Carolina Press, 1978. 174 p.